Hypercrosslinked microporous organic polymer supported metal catalyst and synthesis method and application thereof

Through the synthesis of supercrosslinked microporous organic polymer supported metal catalysts, the problem of low efficiency of existing catalysts in Suzuki reactions is solved, high specific surface area and stability of microporous structure are achieved, and catalytic efficiency is significantly improved.

CN119633899AActive Publication Date: 2025-03-18HUAIHUA UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311668754.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-03-18
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

The existing catalysts are less efficient in Suzuki reactions and are difficult to achieve high specific surface area and stability of micropore structure.

Method used

A supercrosslinked microporous organic polymer supported metal catalyst was used to obtain the catalyst with HCPs-M structure through a multi-step synthesis process by combining 8-hydroxyquinoline and benzene as monomers.

Benefits of technology

A large specific surface area and micropore volume are achieved, which significantly improves the catalytic efficiency of Suzuki reaction, and the catalyst structure is stable, high temperature resistant, and easy to recycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633899A_ABST
    Figure CN119633899A_ABST
Patent Text Reader

Abstract

The invention relates to a super-crosslinked microporous organic polymer supported metal catalyst as well as a synthesis method and application thereof. The super-crosslinked microporous organic polymer supported metal catalyst disclosed by the invention has a relatively large specific surface area, can obtain a relatively good target product yield under the conditions of very small dosage and very short time consumption when being used for heterogeneous catalytic reaction, and has very good catalytic efficiency. Meanwhile, the super-crosslinked microporous organic polymer supported metal catalyst is stable in structure, good in high temperature resistance, easy to recycle and good in reusability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical synthesis, and in particular to a super-crosslinked microporous organic polymer-supported metal catalyst, a synthesis method and application thereof. Background Art

[0002] The development of porous materials has gone through several stages, from natural zeolites in nature, to synthetic molecular sieves, to organic-inorganic hybrid materials (MOFs), and the rise of microporous organic materials (MOPs). Compared with the previous porous materials, MOPs are porous organic polymer skeletons composed entirely of lighter organic elements through covalent bonds. Compared with molecular sieves and MOFs, it has the advantages of lighter weight, more stability, easier generation and modification, and thus has become a porous material with development potential. MOPs are porous organic materials with a pore size of less than 2nm. Because they combine the advantages of porous materials and polymers, they have attracted widespread attention from the academic community. In the past decade or so, the research on MOPs has made significant progress, and gradually developed into four major categories: hyper-crosslinked microporous polymers (HCPs), self-microporous polymers (PIMs), conjugated microporous polymers (CMPs) and covalent organic networks (COFs).

[0003] Hyper-crosslinked polymers (HCPs) are an important branch of microporous organic polymers. They have the characteristics of high specific surface area, wide monomer sources, good thermal stability, and mild synthesis conditions. They are the first microporous organic materials to be industrially produced so far, and have attracted a lot of research interest from scientific researchers. At present, the synthesis strategies of HCPs materials include the following three methods: 1) post-crosslinking of styrene precursors; 2) self-condensation of small molecule monomers; 3) external crosslinker weaving method; 4) Scholl coupling reaction; 5) solvent weaving method. As a new preparation technology, the external crosslinker weaving method has the following advantages: 1) a wide range of monomer sources and flexible and diverse synthesis methods; 2) mild synthesis conditions, cheap monomers and reagents, and can be used for large-scale production of hyper-crosslinked polymers; 3) can be used to prepare polymers with high specific surface area, rich microporous structures and / or multiple functional groups; 4) using monomers with different structures and adjusting the ratio of crosslinkers to prepare polymers with different structures. Summary of the invention

[0004] Based on this, the main purpose of the present invention is to provide a hyper-crosslinked microporous organic polymer-supported metal catalyst and its application in the Suzuki reaction to achieve better catalytic effect.

[0005] A hyper-crosslinked microporous organic polymer-supported metal catalyst and its application in Suzuki reaction, wherein the hyper-crosslinked microporous organic polymer-supported metal catalyst has a structure shown in the following formula HCPs-M:

[0006]

[0007] in:

[0008] M is a transition metal cation, X is an anion, and n=0 or 1.

[0009] In some embodiments, the transition metal cation is Pd 2+ 、Ni 3+ or Cu 2+ , the anion is Cl - Br - 、NO2 - 、CH3COO - CF3COO - .

[0010] The present invention also aims to provide a method for synthesizing the above-mentioned hyper-crosslinked microporous organic polymer-supported metal catalyst, the method comprising the following steps:

[0011] (1) Compound 1 and Compound 2 are added to an organic solvent A, heated, and stirred to obtain a mixture system; the Compound 1 is 8-hydroxyquinoline; and the Compound 2 is benzene with unsubstituted or substituted hydrogen;

[0012] (2) adding Lewis acid B to the mixed system, first heating at low temperature, then heating at high temperature, cooling, drying, extracting, and obtaining hyper-crosslinked polymers HCPs;

[0013] (3) Take the hyper-crosslinked polymer HCPs, add transition metal salt and organic solvent C, heat, stir, cool, dry, extract, and obtain hyper-crosslinked polymer HCPs-M.

[0014] In some embodiments, the organic solvent A in step (1) is a halogenated alkane, preferably 1,2-dichloroethane, chloroform, or carbon tetrachloride.

[0015] In some of the embodiments, the Lewis acid B in step (2) is FeCl3, AlCl3, BiCl3, ZnCl2, BF3·OEt2, preferably BiCl3 and FeCl3.

[0016] In some embodiments, in step (2), the low-temperature heating is at a temperature of 30-35°C, and the heating time is 4-6 hours; the high-temperature heating is at a temperature of 80-85°C, and the heating time is 24-48 hours.

[0017] In some embodiments, the organic solvent C in step (3) is THF or DMF, the heating temperature is 75-85° C., and the heating time is 18-24 h.

[0018] In some embodiments, in step (3), the extraction is carried out by Soxhlet extraction, the solvent is methanol, and the extraction time is 24-48 hours.

[0019] The present invention also aims to provide the use of the above-mentioned hyper-crosslinked microporous organic polymer-supported metal catalyst as a catalyst.

[0020] In some embodiments, the catalyst is used to catalyze the Suzuki reaction, which refers to the reaction of compound I and compound II to form compound III; wherein the structures of compounds I to III are as follows:

[0021]

[0022] Where R 1 , R 2 are independently selected from H, alkyl, alkoxy, halogen or cyano, and Y is Br or I.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The hyper-crosslinked microporous organic polymer-supported metal catalyst shown in the structural formula of the present invention has a large specific surface area, especially a micropore specific surface area and a micropore volume. When used in a heterogeneous catalytic reaction, a good yield of the target product can be obtained with a small amount and a short time consumption, and has a good catalytic efficiency. At the same time, the hyper-crosslinked microporous organic polymer-supported metal catalyst has a stable structure, good high temperature resistance, easy recycling, and good reusability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The morphology of HCPs-I, HCPs-Ⅱ, HCPs-ⅡI and HCPs-I-Pd, HCPs-Ⅱ-Pd and HCPs-ⅡI-Pd of Example 1 obtained by scanning electron microscopy;

[0026] Figure 2 Element distribution diagrams of HCPs-I, HCPs-II, HCPs-I-Pd and HCPs-II-Pd of Example 1 obtained by scanning electron microscopy;

[0027] Figure 3 The morphology of HCPs-I, HCPs-II, HCPs-I-Pd and HCPs-II-Pd of Example 1 obtained by transmission electron microscopy;

[0028] Figure 4 The results of testing HCPs-I, HCPs-II and HCPs-I-Pd and HCPs-II-Pd of Example 1 by infrared spectroscopy are shown in FIG.

[0029] Figure 5 The result diagram of BingingEnergy test on HCPs-I, HCPs-II and HCPs-I-Pd and HCPs-II-Pd of Example 1;

[0030] Figure 6 The H NMR spectrum of compound III-a;

[0031] Figure 7 Carbon NMR spectrum of compound III-a. DETAILED DESCRIPTION

[0032] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0034] The embodiment of the present invention provides a hyper-crosslinked microporous organic polymer-supported metal catalyst, wherein the hyper-crosslinked microporous organic polymer-supported metal catalyst has a structure shown in the following formula HCPs-M:

[0035]

[0036] in:

[0037] M is a transition metal cation, X is an anion, and n=0 or 1.

[0038] Preferably, the transition metal cation M is Pd 2+ 、Ni 3+ or Cu 2+ , the anion is Cl - Br - 、NO2 - 、CH3COO - CF3COO - .

[0039] More preferably, the transition metal cation M is Pd 2+ , the anion is Cl - and CH3COO - .

[0040] The present invention also aims to provide a method for synthesizing the above-mentioned hyper-crosslinked microporous organic polymer-supported metal catalyst, the method comprising the following steps:

[0041] (1) Compound 1 and Compound 2 are added to an organic solvent A, heated, and stirred to obtain a mixture system; the Compound 1 is 8-hydroxyquinoline; and the Compound 2 is benzene with unsubstituted or substituted hydrogen;

[0042] (2) adding Lewis acid B to the mixed system, first heating at low temperature, then heating at high temperature, cooling, drying, extracting, and obtaining hyper-crosslinked polymers HCPs;

[0043] (3) Take the hyper-crosslinked polymer HCPs, add transition metal salt and organic solvent C, heat, stir, cool, dry, extract, and obtain hyper-crosslinked polymer HCPs-M.

[0044] Preferably, the organic solvent A in step (1) is 1,2-dichloroethane, chloroform or carbon tetrachloride.

[0045] Preferably, the Lewis acid B in step (2) is BiCl3 and FeCl3.

[0046] Preferably, in step (2), the low-temperature heating is at a temperature of 30-35°C, and the heating time is 4-6 hours; the high-temperature heating is at a temperature of 80-85°C, and the heating time is 24-48 hours.

[0047] Preferably, in step (3), the organic solvent C is DMF, the heating temperature is 80° C., and the heating time is 18-24 h.

[0048] Preferably, in step (3), the extraction is carried out by Soxhlet extraction, the solvent is methanol, and the extraction time is 24-48 hours.

[0049] The present invention also aims to provide the use of the above-mentioned hyper-crosslinked microporous organic polymer-supported metal catalyst as a catalyst.

[0050] Preferably, the hyper-crosslinked microporous organic polymer-supported metal catalyst is used to catalyze the Suzuki reaction.

[0051] Example 1

[0052] This embodiment provides a hyper-crosslinked microporous organic polymer-supported metal catalyst and a synthesis method thereof.

[0053] The super-crosslinked microporous organic polymer-supported metal catalyst has a structure shown in the following formula HCPs-M:

[0054]

[0055] The synthesis method of the hyper-crosslinked microporous organic polymer-supported metal catalyst HCPs-I-Pd comprises the following steps:

[0056] (1) First, take 0.5975 g (4.12 mmol) of 8-hydroxyquinoline monomer into a round-bottom flask, then add 1.2165 g (15.60 mmol) of benzene solution into the round-bottom flask, and slowly add 40 mL of chloroform. The mouth of the flask is connected to a catheter with a ground-mouth adapter, and the catheter is connected to an oil bubbler to prevent excessive pressure in the reactor from spraying or exploding.

[0057] The above system was placed in a 35°C water bath temperature-controlled, timed digital display magnetic stirrer for heating and stirring, and 4.3601 g (32.70 mmol) of anhydrous aluminum chloride was slowly added to the system while heating. The temperature was gradually raised to 45°C and allowed to react for 5.0 h, then raised to 80°C and reacted for 40 h.

[0058] After the reaction is completed, stop stirring, take out the round-bottom flask, cool the round-bottom flask to room temperature, rinse the product 5-6 times with ethanol solution, take out the product, dry it, and obtain the cross-linked product. After drying, perform Soxhlet extraction (methanol as solvent) on the product for 36 hours.

[0059] After Soxhlet extraction, the hyper-crosslinked polymer HCPs-I was obtained after drying in a vacuum oven.

[0060]

[0061] (2) Take 0.25 g of hyper-crosslinked polymer HCPs and add it into a round-bottom flask, then add 0.037 g (0.17 mmol) of Pd(OAc)2, and finally slowly add 10 mL of DMF solution into the round-bottom flask. After sealing, place it in a 60°C oil bath with a temperature-controlled digital magnetic stirrer for heating and stirring for 24 h. After the reaction is completed, stop stirring, take out the round-bottom flask, and cool it to room temperature.

[0062] The cooled system was filtered, and the obtained solid was washed with acetone three times, using 5 mL of acetone each time. After drying, the solid was subjected to Soxhlet extraction (methanol as solvent) for 36 hours. After the extraction, the super-cross-linked microporous organic polymer-supported metal catalyst HCPs-I-Pd was obtained by vacuum drying.

[0063]

[0064] The synthesis method of the hyper-crosslinked microporous organic polymer-supported metal catalyst HCPs-Ⅱ-Pd comprises the following steps:

[0065] (1) First, take 0.6083 g (4.19 mmol) of 8-hydroxyquinoline monomer into a round-bottom flask, then add 1.2061 g (15.46 mmol) of benzene solution and 3.25 g (42.72 mmol) of dimethoxymethane (FDA) into the round-bottom flask, and slowly add 100 mL of 1,2-dichloroethane. The mouth of the flask is connected to a catheter with a ground-mouth adapter, and the catheter is connected to an oil bubbler to prevent excessive pressure in the reactor from spraying or exploding.

[0066] The above system was placed in a 35°C water bath temperature-controlled, timed digital display magnetic stirrer for heating and stirring, and 3.3841 g (20.86 mmol) of anhydrous ferric chloride was slowly added to the system while heating. The temperature was gradually raised to 45°C and allowed to react for 5.0 h, and then the temperature was raised to 80°C for reaction for 48 h.

[0067] After the reaction is completed, stop stirring, take out the round-bottom flask, cool the round-bottom flask to room temperature, rinse the product with ethanol solution 5-6 times, take out the product, dry it, and obtain the cross-linked product. Perform Soxhlet extraction (methanol as solvent) on the product for 48 hours.

[0068] After Soxhlet extraction, the hyper-crosslinked polymer HCPs-Ⅱ was obtained after drying in a vacuum oven.

[0069]

[0070] (2) Take 0.25 g of hyper-crosslinked polymer HCPs and add it to a round-bottom flask, then add 0.037 g (0.17 mmol) of Pd(OAc), and finally slowly add 10 mL of tetrahydrofuran solution to the round-bottom flask. After sealing, place it in a 60°C oil bath with a temperature-controlled digital magnetic stirrer and heat and stir to react for 24 h. After the reaction is completed, stop stirring, take out the round-bottom flask, and cool it to room temperature.

[0071] The cooled system was filtered, and the obtained solid was washed with acetone for 3 times, using 5 mL of acetone each time, and then dried. After drying, the solid was extracted with Soxhlet (methanol as solvent) for 48 hours. After the extraction, the super-cross-linked microporous organic polymer-supported metal catalyst HCPs-Ⅱ-Pd was obtained by drying.

[0072]

[0073] The synthesis method of the hyper-crosslinked microporous organic polymer-supported metal catalyst HCPs-ⅡI-Pd comprises the following steps:

[0074] (1) First, take 0.6083 g (4.19 mmol) of 8-hydroxyquinoline monomer into a round-bottom flask, then add 1.2061 g (15.46 mmol) of benzene solution and 3.25 g (42.72 mmol) of dimethoxymethane (FDA) into the round-bottom flask, and slowly add 100 mL of 1,2-dichloroethane. The mouth of the flask is connected to a catheter with a ground-mouth adapter, and the catheter is connected to an oil bubbler to prevent excessive pressure in the reactor from spraying or exploding.

[0075] The above system was placed in a 35°C water bath temperature-controlled timed digital display magnetic stirrer for heating and stirring, and 0.63 g (2.0 mmol) of anhydrous BiCl3 was slowly added to the system while heating. The temperature was gradually raised to 45°C and allowed to react for 5.0 h, and then the temperature was raised to 80°C for reaction for 48 h.

[0076] After the reaction is completed, stop stirring, take out the round-bottom flask, cool the round-bottom flask to room temperature, rinse the product 5-6 times with ethanol solution, take out the product, dry it, and obtain the cross-linked product. Perform Soxhlet extraction (methanol as solvent) on the product for 48 hours.

[0077] After Soxhlet extraction, the super-crosslinked polymer HCPs-ⅡI was obtained after drying in a vacuum oven.

[0078]

[0079] (2) Take 0.25 g of hyper-crosslinked polymer HCPs and add it to a round-bottom flask, then add 0.037 g (0.17 mmol) of Pd(OAc), and finally slowly add 10 mL of tetrahydrofuran solution to the round-bottom flask. After sealing, place it in a 60°C oil bath with a temperature-controlled digital magnetic stirrer and heat and stir to react for 24 h. After the reaction is completed, stop stirring, take out the round-bottom flask, and cool it to room temperature.

[0080] The cooled system was filtered, and the obtained solid was washed with acetone for 3 times, using 5 mL of acetone each time, and then dried. After drying, the solid was extracted with a Soxhlet extractor using methanol as a solvent for 48 hours. After the extraction, the super-cross-linked microporous organic polymer-loaded metal catalyst HCPs-ⅡI-Pd was obtained by drying.

[0081]

[0082] The synthesis method adopted by the invention is simple, has mild conditions and high yield.

[0083] Example 2

[0084] This example mainly tests the hyper-crosslinked microporous organic polymer-loaded metal catalysts HCPs-I-Pd and HCPs-II-Pd provided in Example 1, and the unloaded metal precursors HCPs-I and HCPs-II.

[0085] 1. In this example, the morphology of HCPs and HCPs-Pd was observed by scanning electron microscopy. Figure 1 .according to Figure 1 The scanning electron micrographs in show that HCPs-Ⅰ-Pd, HCPs-Ⅱ-Pd and HCPs-ⅡⅠ-Pd have no specific morphology, they are irregularly stacked spherical particles;

[0086] 2. This example uses a scanning electron microscope to observe the distribution of four elements: C, N, O, and Pd. The test results are shown in Figure 2 . Figure 2 The presence and uniform distribution of Pd in ​​both samples were confirmed.

[0087] 3. This example also uses a transmission electron microscope to observe the morphology of HCPs and HCPs-Pd. The test results are shown in Figure 3 .according to Figure 3 The transmission electron microscopy images in the figure confirm the presence of Pd on the hyper-crosslinked microporous organic polymer-supported metal catalyst, and determine that the lattice spacing of about 0.2 nm is that of the Pd species, which is uniformly distributed in the sample.

[0088] Fourth, this example also uses infrared spectroscopy to test HCPs and HCPs-Pd. The test results are shown in Figure 4 .according to Figure 4 , HCPs-Ⅰ-Pd sample at 1624, 1492, 877 and 736 cm -1 The infrared peak intensity at the position of HCPs-Ⅰ increased; comparing the HCPs-Ⅱ and HCPs-Ⅱ-Pd curves, it was found that the infrared peaks of HCPs-Ⅱ-Pd were at 782 and 736 cm -1 It is a single infrared peak (741 cm -1 ), the peak intensity is also at 606cm -1 These changes are all caused by the coordination of Pd on HCPs.

[0089] 4. This example also tests HCPs and HCPs-Pb by Binging Energy. The test results are shown in Figure 5 . Figure 5The XPS survey spectra of the characteristic peaks of Pd 3d and C1s at binding energies of 338.1 and 284.8 eV, respectively, are depicted in A. It can be observed that both HCPs-Ⅰ-Pd and HCPs-Ⅱ-Pd exhibit characteristic peaks of Pd. Figure 5 B shows the XPS spectra of Pd of HCPs-I-Pd and HCPs-II-Pd samples, and the peaks at binding energies of 343.7 and 338.2 eV are associated with the presence of Pd(II). It can be determined that Pd has successfully coordinated with HCPs to form HCPs-Pd.

[0090] Example 3

[0091] This example evaluates the performance of the super-crosslinked microporous organic polymer-supported metal catalyst (HCPs-Pd) having a structure shown in the formula HCPs-M provided in Example 1 as a catalyst. Taking the preparation process of the Suzuki coupling reaction of bromobenzene and phenylboronic acid as an example:

[0092]

[0093] First, 0.7801 g (5.0 mmol) of bromobenzene and 0.7930 g (6.5 mmol) of phenylboric acid were added to a round-bottom flask, and 1.6960 g (8.0 mmol) of potassium phosphate and 20 mg of a heterogeneous catalyst (HCPs-Pd) were added thereto. Then, ethanol: water was added to the system in a ratio of 4:1 (i.e., 16 mL of ethanol and 4 mL of water). After nitrogen protection, the round-bottom flask was placed in an 80°C oil bath with a temperature-controlled, timed digital display magnetic stirrer and heated with stirring for 3.0 h. After the reaction was completed, stirring was stopped, the round-bottom flask was taken out, cooled to room temperature, the catalyst (HCPs-Pd) was filtered and recovered, and the liquid was naturally dried to obtain a solid powder.

[0094] Add 5 mL of dichloromethane and 6 g of silica gel powder to the powder, stir evenly, and air dry for use. The silica gel powder and the product system are separated by column, and the separated liquid is collected in another round-bottom flask. The collected liquid is rotary evaporated by a rotary evaporator until a small amount of liquid is left in the round-bottom flask, and the rotary evaporation is stopped. Wait for it to dry naturally, collect the product III-a after drying, and calculate the yield.

[0095] Figure 6 The hydrogen nuclear magnetic resonance spectrum of compound III-a, Figure 7 Carbon NMR spectrum of compound III-a. Figure 6 and Figure 7 The synthesis of compound III-a was confirmed.

[0096] The results are shown in Table 1 below:

[0097] Table 1

[0098]

[0099] a Reaction conditions: 5.0 mmol bromobenzene, 6.5 mmol phenylboric acid, 8.0 mmol base, 20 mg HCPs-Pd catalyst, 3.0 h, 80 ° C, nitrogen protection. b 40 mgHCPs-Pd catalyst. c 10 mg HCPs-Pd catalyst. d 1.0 h. e No nitrogen protection. f React at room temperature for 12.0 hours.

[0100] Example 4

[0101] This example evaluates the application scope of the hyper-crosslinked microporous organic polymer-supported metal catalyst (HCPs-Pd) having a structure represented by the formula HCPs-M provided in Example 1 as a catalyst in the Suzuki reaction.

[0102] The reaction formula of the present embodiment is as follows:

[0103]

[0104] The specific reactant structures are shown in Table 2:

[0105] Table 2

[0106]

[0107] Reaction conditions: 5.0 mmol bromobenzene, 6.5 mmol phenylboric acid, 8.0 mmol base, 20 mg HCPs-Pd catalyst, 3.0 h, 80 ° C, nitrogen protection.

[0108] Example 5

[0109] This embodiment is a variation of embodiment 3. The main variation relative to the embodiment is that the adopted hyper-crosslinked microporous organic polymer-supported metal catalyst has a structure shown in the following formula HCPs-M:

[0110]

[0111] The preparation of the super-crosslinked microporous organic polymer-supported metal catalyst is based on Example 1, except that the palladium acetate in Example 1 is replaced by nickel bromide.

[0112] The results are shown in Table 3:

[0113] Table 3

[0114]

[0115] Reaction conditions: 5.0 mmol bromobenzene, 6.5 mmol phenylboric acid, 8.0 mmol base, 50 mg catalyst, 3.0 h, 80 ° C, nitrogen protection.

[0116] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0117] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. Application of a hyper-crosslinked microporous organic polymer-supported metal catalyst in Suzuki reaction, characterized in that: The hyper-crosslinked microporous organic polymer-supported metal catalyst has a structure shown in the following formula HCPs-M: in: M is a transition metal cation, X is an anion, and n=0 or 1.

2. The hyper-crosslinked microporous organic polymer-supported metal catalyst according to claim 1, characterized in that: The transition metal cation M is Pd 2+ 、Ni 3+ or Cu 2+ , the anion is Cl - Br - 、NO2 - 、CH3COO - CF3COO - .

3. A method for synthesizing a hyper-crosslinked microporous organic polymer-supported metal catalyst HCPs-M, characterized in that: The synthesis method comprises the following steps: (1) Compound 1 and Compound 2 are added to an organic solvent A, heated, and stirred to obtain a mixture system; the Compound 1 is 8-hydroxyquinoline; and the Compound 2 is benzene with unsubstituted or substituted hydrogen; (2) adding Lewis acid B to the mixed system, first heating at low temperature, then heating at high temperature, cooling, drying, and extracting to obtain hyper-crosslinked polymers HCPs; (3) Take the hyper-crosslinked polymer HCPs, add transition metal salt and organic solvent C, heat, stir, cool, dry, extract, and obtain hyper-crosslinked polymer HCPs-M.

4. The method for synthesizing a hyper-crosslinked microporous organic polymer-supported metal catalyst according to claim 3, characterized in that: The organic solvent A described in step (1) is a halogenated alkane, preferably 1,2-dichloroethane, chloroform, or carbon tetrachloride.

5. The method for synthesizing a hyper-crosslinked microporous organic polymer-supported metal catalyst according to claim 3, characterized in that: The Lewis acid B described in step (2) is FeCl3, AlCl3, BiCl3, ZnCl2, BF3·OEt2, preferably BiCl3 and FeCl3.

6. The method for synthesizing a hyper-crosslinked microporous organic polymer-supported metal catalyst according to claim 3, characterized in that: In step (2), the low-temperature heating is performed at a temperature of 30-35°C and the heating time is 4-6 hours; the high-temperature heating is performed at a temperature of 80-85°C and the heating time is 24-48 hours.

7. The method for synthesizing a hyper-crosslinked microporous organic polymer-supported metal catalyst according to claim 3, characterized in that: In step (3), the organic solvent C is THF or DMF, the heating temperature is 75-85° C., and the heating time is 18-24 h.

8. The method for synthesizing a hyper-crosslinked microporous organic polymer-supported metal catalyst according to claim 3, characterized in that: In step (3), the extraction is carried out by Soxhlet extraction, the solvent is methanol, and the extraction time is 24-48 hours.

9. The use according to claim 1, characterized in that The Suzuki reaction refers to the reaction of compound I and compound II to generate compound III; wherein the structures of compounds I to III are as follows: Where R 1 , R 2 are independently selected from H, alkyl, alkoxy, halogen or cyano, and Y is Br or I.

Citation Information

Patent Citations

  • Super-crosslinked metal polymer, and application thereof in Suzuki coupling reaction

    CN110835413A

  • Cross-linked high polymer containing 8-hydroxyquinoline metal complex and its preparation and use

    CN1594403A

  • Modified porous hypercrosslinked polymers for co2 capture and conversion

    US20180050328A1

  • A gas-adsorbing porous aromatic hyper-cross-linked polymer and a method of preparing thereof

    WO2016147116A1